Atonal homolog 8/Math6 regulates differentiation and maintenance of skeletal muscle - Divvela, Satya Srirama Karthik; Offei, Eric Bekoe; Suerland, Florian; Revuelta García, David; Kwiatkowski, Julia; Balakrishnan-Renuka, Ajeesh; Bohne, Pauline; Böing, Marion; Morosan-Puopolo, Gabriela; Mark, Melanie D.; Brand-Saberi, Beate (Frontiers in Cell and Developmental Biology, 2022)
Atonal Homolog 8 (Atoh8) belongs to a large superfamily of transcriptional regulators called basic helix-loop-helix (bHLH) transcription factors. Atoh8 (murine homolog ‘Math6’) has been shown to be involved in organogenesis during murine embryonic development. We have previously identified the expression of Atoh8 during skeletal myogenesis in chicken where we described its involvement in hypaxial myotome formation suggesting a regulatory role of Atoh8 in skeletal muscle development. Within the current study, we analyzed the effect of the loss of function of Atoh8 in murine primary myoblasts and during differentiation of pluripotent stem cells into myotubes, and the effect of its gain of function in C2C12 cells. Based on the observed results, we conclude that Atoh8 regulates myoblast proliferation via modulating myostatin signaling. Further, our data revealed a reduced muscle mass, strength and fiber size with significant changes to the muscle fiber type suggesting atrophy in skeletal muscle of Atoh8 mutants. We further report that Atoh8 knockout mice suffer from a condition similar to ambient hypoxia which may be the primary cause of the phenotype. Altogether, this study shows the significance of Atoh8 not only in myogenesis but also in the maintenance of skeletal muscle.